2018
DOI: 10.3390/f9070430
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Carbon Fraction, Density, and Carbon Density in Conifer Tree Tissues

Abstract: Abstract:We analyzed variations in three tree properties: tissue density, carbon fraction, and carbon density within bole tissues of nine Californian conifer species. Model performance for all three tree properties was significantly improved with the addition of covariates related to crown characteristics and position within the tree. This suggests that biomass and carbon mass estimates that rely on fixed wood density and carbon fraction may be inaccurate across tree sizes. We found a significant negative rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Our study uncovers the following general patterns in CFs across dead wood globally: (A) lower dead wood CFs in tropical vs. other forest biomes, (B) lower dead wood CFs in angiosperms vs. gymnosperms, and (C) higher dead wood CFs in bark vs. other tissues (Table 1 ). These results are consistent with studies on live wood CF variability 18 , 32 , 33 , 35 , 47 , and perhaps are not surprising given the statistically significant relationship between dead and live wood CFs observed in a subset of tree species evaluated here (Supplementary Fig. 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study uncovers the following general patterns in CFs across dead wood globally: (A) lower dead wood CFs in tropical vs. other forest biomes, (B) lower dead wood CFs in angiosperms vs. gymnosperms, and (C) higher dead wood CFs in bark vs. other tissues (Table 1 ). These results are consistent with studies on live wood CF variability 18 , 32 , 33 , 35 , 47 , and perhaps are not surprising given the statistically significant relationship between dead and live wood CFs observed in a subset of tree species evaluated here (Supplementary Fig. 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Data on CF from live trees also suggest that tissue-specific variability in dead wood CF will be pronounced. Specifically, there is likely to be especially high CFs in bark vs. other tissues, due to their high concentrations of C-rich and recalcitrant compounds such as lignin, suberin, and tannins 32 35 . Finally, the position of dead wood—that is, standing vs. downed—may also influence CFs 12 , but hypotheses and findings related to this are mixed with some research suggesting that standing dead wood has higher CFs vs. downed wood 26 , while other lines of evidence suggest the opposite 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon content ((CC), also referred to as carbon fraction or carbon concentration) is known to vary with tree species [4][5][6][7][8][9][10], wood tissues [4,5,7,[10][11][12][13][14], canopy position and tree size [15,16], and life-history traits (e.g., shade tolerance) [12]. Stand density management practices, used for the sustainable production of renewable forest fiber, increase radial growth rates with increased intensity of thinning [17,18] and initial spacing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Wood C concentrations – defined as the unit mass of C per unit mass of dry wood, and the focus of our research here – is a wood trait that has recently received research attention. Studies have demonstrated that wood C is highly variable across tree species (Lamlom & Savidge, 2003; Martin & Thomas, 2011; Gao et al ., 2016; Jones & O’Hara, 2018), with a recent global meta‐analysis indicating that wood C concentrations range from 28 to 65% (on mass per mass basis) across species and tissue types (Martin et al ., 2018). This same meta‐analysis reported a global average wood C concentration of 47.6 ± 0.9% (SE) across all tree species and tissues – a value that differs substantially from the 50% wood C concentration value that is commonly assumed in forest C accounting protocols (Martin et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%